2001
DOI: 10.1111/j.1572-0241.2001.04139.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cytokines, inducible nitric oxide synthase, and matrix metalloproteinases in pouchitis: effects of probiotic treatment

Abstract: The ability of antibiotic and probiotic treatments to increase tissue levels of IL-10, at a higher level than those observed in control pouches, and to decrease, to levels present in control pouches, proinflammatory cytokine, inducible nitric oxide synthase, and matrix metalloproteinase activity may suggest a mechanism of action to explain the efficacy of this therapeutic regime in pouchitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
48
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(53 citation statements)
references
References 69 publications
4
48
0
1
Order By: Relevance
“…VSL#3 contains, in addition to bifidobacteria, a combination of several species of lactobacilli, in different proportions but at very high concentrations. It has been shown that VSL#3 administration at a high dose can maintain antibiotic-induced remission in patients with pouchitis [17] by increasing local production of IL-10 [23]. Our study also suggests that the protection from autoimmune diabetes by VSL#3 oral administration is dominant and is achieved mostly through the induction of regulatory cells.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…VSL#3 contains, in addition to bifidobacteria, a combination of several species of lactobacilli, in different proportions but at very high concentrations. It has been shown that VSL#3 administration at a high dose can maintain antibiotic-induced remission in patients with pouchitis [17] by increasing local production of IL-10 [23]. Our study also suggests that the protection from autoimmune diabetes by VSL#3 oral administration is dominant and is achieved mostly through the induction of regulatory cells.…”
Section: Discussionsupporting
confidence: 56%
“…In previous studies, the administration of different lactobacilli resulted in the modulation of local and systemic immune responses in humans and animal models [19,23,45,46]. This effect is thought to be accomplished through the occurrence of several different biological events [18,[47][48][49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ulisse et al 42 showed that antibiotic treatment in patients with pouchitis, although able to induce clinical remission, is not able to completely restore normal levels of the cytokine-inducible nitric oxide synthetase (iNOS), and metalloproteinase enzymes activity as observed in patients without pouchitis. L. rhamnosus GG induces expression of iNOS gene and enhance the production of the proinflammatory cytokine tumor necrosis factor-␣, which in turn may be responsible for the downregulation of iNOS and metalloproteinase activity.…”
Section: Discussionmentioning
confidence: 97%